IN A POLYLINGUAL ENVIRONMENT PRAGMATIC COMPETENCE CONCEPT AND ITS IMPORTANCE OF DEVELOPMENT - Rustam Yuldoshev o’g’li (Western European Studies, 2024)
This article reveals a theoretical discussion about the introduction of concrete pragmatic teaching as a tool to help develop pragmatic competence in a foreign language. The concept of pragmatic competence was analyzed based on theoretical and empirical approaches. The theoretical basis of the development of pragmatic competence, which is part of the discussed communicative competence, is proven by the opinion of scientists
Keywords: pragmatics; competence; pragmatic competence